Effect of dynamic range of motion and static stretching techniques on flexibility, strength and jump performance in female gymnasts - Ferri-Caruana, A.; Roig-Ballester, N.; Romagnoli, M. (Science of Gymnastics Journal, 2020)
The aim of this study was to determine the long term effect of dynamic range of motion (DROM) stretching technique and static stretching (SS) on hip range of motion (ROM), hip isometric strength and vertical jump performance in female gymnasts. In a randomized controlled trial eighteen gymnasts (age 13 ± 2 years) were assigned to a DROM group (n= 9) or SS group (n=9 ). Participants were assessed at baseline and again at completion of the intervention on: hip extensión (HE), hip flexion (HF), 1RM isometric HF strength, squat jump (SJ) and split leap (SL). Results: DROM group improved statistically from pre- to post-test in right leg HE ROM (13.67 ± 4.7 vs. 21.22 ± 5.2), right leg HF ROM (129.9 ± 9.9 vs. 139.0 ± 10.4), hip isometric strength for the right leg (2.0 ± 1.1 vs. 4.7 ± 1.6) and the left leg (1.7 ± 0.7 vs. 4.1 ± 1.6). Jump performance was not affected by type of stretching. Significance was set at 0.05 (2-tailed) for all analyses. DROM was more effective in improving gymnastic performance variables than SS. Such information may assist in determining the applications of various stretching techniques in flexibility-trained female athletes.